PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR SEGIEMPAT MELALUI MODEL PEMBELAJARAN ELPSA DENGAN PERMAINAN KSD BAGI SISWA KELAS VII A SMPN 2 PATEAN KENDAL SEMESTER 2 TAHUN PELAJARAN 2015/2016 - Mustakim, Mustakim (Jurnal Pendidikan, 2016)
The problems of classroom action research are for students of class VII A SMPN 2 Patean Kendal 2nd Semester Academic Year 2015/2016: (1) Is ELPSA learning with the game KSD can improve learning outcomes Mathematical quadrilateral material?, (2) What ELPSA learning with games KSD can increase the activity of learning mathematics quadrilateral material?, and (3) How to change the behavior of students of class VII A after following learning learning ELPSA with KSD game on material quadrilateral? The study was conducted in two cycles each consisting of planning, implementation, observation, and reflection. Data collected through observation activities, teacher journals, student questionnaire, and test. Subjects were increased activity and results study A class VII SMPN 2 Patean Kendal, amounting to 22 learners with a composition of 12 male students and 10 female student. The study was conducted in January to April 2016. The indicators in this study were (1) More than 75% of students are actively involved in the learning process; (2) The average grade formative test at least 75 to 75% of students reach the minimum KKM is 75; (3) At least 85% of students are well behaved during the learning process. The results showed that (1) increased student learning outcomes seen from the highest value, lowest value, average, and mastery learning. In the first cycle the highest grade 86 increased 14 points to 100 in the second cycle, the lowest value of 54 increased 4 points to 58 in the second cycle, the average value of 74 increased by 12 points to 86, and the learning completeness 51% increase 35% to 86%; (2) All aspects of the students in learning activities is experiencing an increase in both activity visual, oral, listening, writing, drawing, metrics, mentally, and emotionally. The conclusions of this Class Action Research is a learning game ELPSA with KSD on quadrilateral materials can improve learning outcomes and activities as well as change the behavior of students of class VII A SMPN 2 Patean Kendal 2nd Semester Academic Year 2015/2016. Rumusan masalah dalam Penelitian Tindakan Kelas di SMP2 kelas VII A tahunajaran 2015/2016 adalah (1) Apakah pembelajaran ELPSA dengan permainan KSD dapat meningkatkan hasil belajar Matematika materi segiempat Semester 2 Tahun Pelajaran?, (2) Apakah pembelajaran ELPSAdengan permainan KSD dapat meningkatkan aktivitas belajar Matematika materi segiempat?, dan (3) Bagaimana perubahan perilaku siswa Semester 2 setelah mengikuti pembelajaran pembelajaran ELPSA dengan permainan KSD pada materi segiempat? Penelitian dilakukan dalam dua siklus yang  terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Pengumpulan data, melalui pengamatan, jurnal guru, angket siswa, dan tes. Subjek penelitian adalah peningkatan aktivitas dan hasil belajar siswa kelas VII A SMPN 2 Patean Kendal yang berjumlah 22 siswa dengan komposisi 12 siswa putra dan 10 siswa putri. Penelitian dilakukan pada bulan Januari sampai dengan April 2016. Indikator dalam penelitian ini adalah (1) Lebih dari 75% siswa terlibat aktif dalam proses pembelajaran; (2) Rata-rata nilai tes formatif minimal 75 dengan 75% siswa mencapai batas minimal KKM yaitu 75; (3) Minimal 85% siswa berperilaku baik selama mengikuti proses pembelajaran. Hasil penelitian menunjukkan bahwa (1) hasil belajar siswa meningkat dilihat dari nilai tertinggi, nilai terendah, rata-rata, dan ketuntasan belajar. Pada Siklus I nilai tertinggi 86 meningkat 14 point menjadi 100 pada Siklus II, nilai terendah 54 meningkat 4 point menjadi 58 pada Siklus II, rata-rata nilai 74 meningkat 12 point menjadi 86, dan ketuntasan belajar 51% meningkat 35% menjadi 86%.; (2) Semua aspek aktivitas siswa dalam belajar mengalami peningkatan baik aktivitas visual, oral, mendengarkan, menulis, mengambar, metrik, mental, maupun emosional. Simpulannya adalah pembelajaran ELPSA dengan permainan KSD pada materi segiempat dapat meningkatkan hasil belajar dan aktivitas serta mengubah perilaku siswa.